Estructuras auxiliares en contacto: tener + el acuerdo (in)variable del participio en el español de Asturias occidental - Gupton, Timothy (Studia Romanica Posnaniensia, 2004)
The Galician language presents certain peculiarities in its use of ter + participle, allowing for variable agreement of the participle when preceding the verbal complement, yet prohibiting it when following the complement. The consequence of such an auxiliary system upon spoken and written Spanish, in areas in which the two languages cohabit, has yet to be examined. I will show that the regional tongue, Eonavian Galician, spoken in the town of Navia and surrounding areas (Principality of Asturias, Spain), although rapidly disappearing, has affected an analogous and similar system in Spanish, thus creating forms that would be otherwise unacceptable in Standard Spanish and provide syntactic analyses.